The Effectiveness of Dialectical Behavioral Therapy on Emotional Regulation and Marital Conflicts of Women with Borderline Personality Disorder in Isfahan City - Khallili , Nasrin; Khoshakhlagh, Hasan (Shahroud Journal of Medical Sciences, 2022)
Background: This study aimed to investigate the effectiveness of dialectical behavioral therapy on emotional regulation and marital conflicts of women with borderline personality disorder in Isfahan city in Isfahan. Methods: This is a semi-experimental method with pre-test, post-test, and followed with the control group. To conduct the study, 30 women with borderline personality disorder referring to Isfahan Family Therapy Clinics in 2017, who were willing to participate in the study were selected based on criteria of entry and exit and were randomly divided into two experimental groups (15 persons) and control (15 persons) and complete the pretest, Gross & John (2003) and Marital Conflict Questionnaire (MCQ). The experimental group underwent dialectical behavioral therapy at 10 sessions (weekly and 2 hours) and one week after intervention, both experimental and control groups were subjected to post-test. After the completion of the training and post-test, a one-month follow-up period was completed. The repeated measures analysis of variance was performed using SPSS Statistics ver22. The significant level was set at 0.05. Results: The results of repeated measures of variance analysis showed that dialectical behavioral therapy had an effect on emotional regulation and marital conflicts. And leads to improved emotional reactions and reduced marital conflicts in women with borderline personality disorder in Isfahan (p-value<0.001). Conclusions: The effect of this treatment on emotional regulation and marital conflicts of women with borderline personality disorder was stable. As a result, dialectical behavioral therapy as a therapeutic approach is recommended to improve the psychological status of women with borderline personality disorder symptoms. Keywords: Dialectical behavioral therapy, Emotional regulation, Marital conflicts, Borderline personality disorder.